2022
DOI: 10.1111/jcpt.13750
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug–drug interactions: A comparison of online drug interaction databases

Abstract: What is known and objective Antiretrovirals have a high drug interaction potential, which can lead to increased toxicity and/or decreased efficacy. Multiple databases are available to assess drug–drug interactions. The aim of our study was to compare interaction identification for commonly used ARVs and concomitant medications between six different online drug–drug interaction databases. Comment This was a cross‐sectional review using each of the following six databases: LexiComp®, Clinical Pharmacology®, Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, the reporting of real-world DDI data to www.clinicalcasesDDIs.com is highly encouraged as it serves as a valuable resource for assessing the clinical relevance of DDIs. This becomes particularly crucial given the occasionally theoretical and conflicting information present in available electronic databases [6,19]. Documenting real-world cases helps bridge knowledge gaps, ultimately enhancing the quality of care for PWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reporting of real-world DDI data to www.clinicalcasesDDIs.com is highly encouraged as it serves as a valuable resource for assessing the clinical relevance of DDIs. This becomes particularly crucial given the occasionally theoretical and conflicting information present in available electronic databases [6,19]. Documenting real-world cases helps bridge knowledge gaps, ultimately enhancing the quality of care for PWH.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the clinical significance of many DDIs remains uncertain. Furthermore, discrepancies on the relevance of a particular DDI may be found between different databases, further complicating the interpretation of a given potential interaction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, a similar recent study found that Micromedex had among the highest scores for scope and completeness looking at information for off-label uses and infectious disease information [ 13 , 25 ]. Conversely, compared to Clinical Pharmacology and Lexicomp, Micromedex reported fewer drug-drug interactions for assessed antiviral medications in a recent study [ 26 ]. These results, in combination with assessment of user needs and other comparable resources in the collection, will assist health sciences librarians in assessing the appropriateness of continued support of Micromedex despite price increases.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple drug interaction-support web resources are available (including but not limited to LexiComp, Clinical Pharmacology, Micromedex, Liverpool Drug Interactions, and Toronto General Hospital Drug Interaction Tables), a study comparing the use of these resources for ART interactions yielded inconsistent results. 27 Hence, active involvement by a pharmacist to thoroughly review complicated cases of ART-related drug interactions is preferred and has been shown to improve ART adherence and outcomes. 28 …”
Section: Components Of Carementioning
confidence: 99%